2018
DOI: 10.1007/s10530-018-1710-7
|View full text |Cite
|
Sign up to set email alerts
|

Biological invasions increase the richness of arbuscular mycorrhizal fungi from a Hawaiian subtropical ecosystem

Abstract: Biological invasions can have various impacts on the diversity of important microbial mutualists such as mycorrhizal fungi, but few studies have tested whether the effects of invasions on mycorrhizal diversity are consistent across spatial gradients. Furthermore, few of these studies have taken place in tropical ecosystems that experience an inordinate rate of invasions into native habitats. Here, we examined the effects of plant invasions dominated by non-native tree species on the diversity of arbuscular myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 91 publications
(144 reference statements)
0
16
0
Order By: Relevance
“…It is well known that mutualistic microbial diversity of arbuscular mycorrhizal fungi (AMF) remarkably assists in the sustenance of forests. Recently, a few IAPS have been reported to promote the diversity of AMF in Hawaii forests (Gomes et al, 2018). Further, it has been observed that certain IAPS (Centaurea stoebe and Euphorbia esula) increased the abundance as well as diversity of mycorrhizal fungi, which have immense role in ecosystem functioning (Lekberg et al, 2013).…”
Section: Whether All Iaps Are Nuisance? Quest Of Management Implicationsmentioning
confidence: 99%
“…It is well known that mutualistic microbial diversity of arbuscular mycorrhizal fungi (AMF) remarkably assists in the sustenance of forests. Recently, a few IAPS have been reported to promote the diversity of AMF in Hawaii forests (Gomes et al, 2018). Further, it has been observed that certain IAPS (Centaurea stoebe and Euphorbia esula) increased the abundance as well as diversity of mycorrhizal fungi, which have immense role in ecosystem functioning (Lekberg et al, 2013).…”
Section: Whether All Iaps Are Nuisance? Quest Of Management Implicationsmentioning
confidence: 99%
“…[ 25 ], and Vincetoxicum rossicum [ 26 ] did not alter the structure of soil microbial communities. Also, some microcosms exposed to the simultaneous invasion of multiple plant species [ 27 29 ] did not alter soil microbiomes. Similarly, soil microbiome structure in microcosms did not change with the addition of the invasive earthworm Aporrectodea trapezoides [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have investigated the effects of species invasions on environmental microbiomes, we still lack a generalized consensus across different environmental microbiomes and systems. Previous studies have found that invasive species increased environmental microbial diversity [13,19], while others reported a decrease [15,20,29]. However, the majority of studies did not analyze the microbial diversity, as they used techniques that did not allow for such analysis, or reported no changes [9,10,2328,30,11,12,14,1618,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…[25], and Vincetoxicum rossicum [26] did not alter the structure of soil microbial communities. Also, some microcosms exposed to the simultaneous invasion of multiple plant species [2729] did not alter soil microbiomes. Similarly, soil microbiome structure in microcosms did not change with the addition of the invasive earthworm Aporrectodea trapezoides [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation